Understanding Abusive Language in Early Childhood Social Interactions: A Phenomenological Analysis of Contexts, Sources, and Implications - Raya Nurlianharkah; Yuli Kurniawati Sugiyo Pranoto; Petra Kristi Mulyani (AL-ISHLAH: Jurnal Pendidikan, 2026)
The increasing presence of abusive language in early childhood raises concerns due to its potential impact on children’s emotional, social, and moral development. Young children often reproduce such language without understanding its ethical implications, shaped by peer interaction, family environment, and digital media exposure. This study employed a qualitative phenomenological approach to examine the manifestation, contributing factors, and moral implications of abusive language among children aged 4–6 years. Data were collected in an early childhood education institution in East Java through in-depth interviews with teachers and parents, structured observations, and document analysis. Abusive language frequently emerged during emotionally intense situations and peer interactions. Key contributing factors included limited emotional regulation, strong peer influence, permissive parenting styles, and exposure to digital media. Children generally lacked moral awareness of the language used, often interpreting abusive expressions as humorous or as a means of social bonding. The findings suggest that the use of abusive language in early childhood reflects a social learning process not yet supported by mature emotional regulation or moral reasoning. This highlights the need for early, coordinated interventions. Collaborative efforts between families and educational institutions are essential to foster positive communication, strengthen moral development, and guide appropriate language use from an early age.